Microtubule-dependent and independent roles of spastin in lipid droplet dispersion and biogenesis - Tadepalle, Nimesha (Life Sci Alliance, 2020)
Lipid droplets (LDs) are metabolic organelles that store neutral lipids and dynamically respond to changes in energy availability by accumulating or mobilizing triacylglycerols (TAGs). How the plastic behavior of LDs is regulated is poorly understood. Hereditary spastic paraplegia is a central motor axonopathy predominantly caused by mutations in SPAST, encoding the microtubule-severing protein spastin. The spastin-M1 isoform localizes to nascent LDs in mammalian cells; however, the mechanistic significance of this targeting is not fully explained. Here, we show that tightly controlled levels of spastin-M1 are required to inhibit LD biogenesis and TAG accumulation. Spastin-M1 maintains the morphogenesis of the ER when TAG synthesis is prevented, independent from microtubule binding. Moreover, spastin plays a microtubule-dependent role in mediating the dispersion of LDs from the ER upon glucose starvation. Our results reveal a dual role of spastin to shape ER tubules and to regulate LD movement along microtubules, opening new perspectives for the pathogenesis of hereditary spastic paraplegia.